(untitled) - Williams, Melvin H. (New York, 2005)
This textbook provides the reader with thorough coverage of the role nutrition plays in enhancing one's health, fitness and sport performance. Current research and practical activities are incorporated throughout.
Keywords: Nutrition,Physical fitness,Sports,Dinh dưỡng,Phòng tập thể dục thể chất,Thể thao; Physiological aspects,Khía cạnh sinh lý